Faktor-faktor penentu integrasi pasar daging ayam broiler - Jojo; Feriansyah; Kamal Ma'ruf; Ana Frasipa; Isman Sidik (Fakultas Pertanian Universitas Majalengka, 2023)
Broiler chicken meat is a strategic commodity that is growing rapidly. This product occupies the highest consumption rating of meat products. This study examines the factors of broiler chicken market integration in Indonesia. The data used is secondary data for the monthly time series, which is 72 months, in the period January 2015-December 2020. The data were analyzed using multiple linear regression analysis approaches. The results show that a significant variable affects the integration of the broiler chicken meat market in Indonesia: the amount of production in the destination province.